The diagnostic value and efficacy evaluation of lung ultrasound score in neonatal respiratory distress syndrome: a prospective observational study - Dong, Jian; Deng, Yuhong; Tong, Jin; Du, Tingting; Liu, Wenguang; Guo, Yan (Frontiers in Pediatrics, 2025)
ObjectiveTo evaluate the diagnostic efficacy and determine the optimal cut-off values of lung ultrasound score for diagnosing neonatal respiratory distress syndrome and its accuracy in assessing the efficacy of neonatal respiratory distress syndrome.MethodThis prospective study included 100 neonates with suspected neonatal respiratory distress syndrome. Each patient underwent both the 14-zone and 12-zone lung ultrasound methods, as well as a chest x-ray, performed after birth and before initiating drug treatment. Surfactant replacement therapy was administered to patients who were diagnosed with neonatal respiratory distress syndrome and met the criteria for medication. Lung ultrasound was conducted and recorded at the 24th hour, the 48th hour, the 72nd hour, and the 7th day after drug administration. ROC curve analysis, Kappa statistics, and ANOVA were utilized to identify the optimal cut-off values for the lung ultrasound scores in diagnosing neonatal respiratory distress syndrome.Results89 neonates were diagnosed with respiratory distress syndrome, of whom 64 received surfactant replacement therapy. The mean scores of 12-zone lung ultrasound score, 14-zone lung ultrasound score, and chest x-ray score are 18.22 ± 7.15, 38.92 ± 9.69, and 2.15 ± 0.97, respectively. The diagnostic AUC for the 12-zone lung ultrasound score is 0.84 (95% CI: 0.73–0.95), with an optimal cut-off value of 13.5 for diseased vs. not diseased, while the AUC for the 14-zone lung ultrasound score is 0.88 (95% CI: 0.76–0.99), with an optimal cut-off value of 34 for diseased vs. not diseased. There is significant concordance between the neonatal lung ultrasonography scores and the chest x-ray score for diagnosis respiratory distress syndrome (P < 0.01). The optimal cut-off values for the grading diagnosis of neonatal respiratory distress syndrome using the 14-zone lung ultrasound score are identified as 36.5, 40.5, and 44.5. The 12-zone lung ultrasound score does not have a significant difference between the 12th hour after receiving surfactant replacement therapy and the 48th hour after treatment (P = 0.08). All other comparisons demonstrated significant differences.ConclusionThe 14-zone lung ultrasound score demonstrates higher diagnostic efficacy in diagnosing neonatal respiratory distress syndrome and can accurately evaluate the early efficacy of surfactant replacement therapy in neonates.